Sustainability training at Spanish public faculties of education: a virtual ethnography - Antonio Nadal Masegosa; Lucía Rodríguez-Olay (Tópicos Educacionais)
Various institutional statements and official documents refer to the Sustainable Development Goals and sustainability training. This should imply a university education in these values, considering that those who are going to train the new generations, in the Spanish State, must pass through the faculties of education.